Physical Activity Patterns and Perceptions among Type 2 Diabetic and Non-diabetic Portuguese - Maria Dulce Leal Esteves; Ricardo José Ascensão Gouveia Rodrigues; Paulo Gonçalves Pinheiro; Rui Miguel Marques Brás; Ana Isabel Antunes Dias Rodrigues Gouveia; Kelly de Lemos Serrano o´Hara; Paulo Alexandre de Oliveira Duarte (The Society of Aging and Physical Activity (SAPA), 2019)
Background. The increasing prevalence and incidence of type 2 Diabetes has turned it into a worldwide epidemic. Although Physical Activity (PA) may play an essential role in the prevention and management of this disease, sedentary lifestyles continue to increase among diabetics. Besides, there is evidence to believe that diabetics and non-diabetics show different patterns of PA behavior, perceptions and information seeking. Objectives. This study aims to analyze diabetics and non-diabetics differences regarding (1) PA patterns (level, barriers, goals/expectations and preferred activities); (2) PA-related information sources and (3) evidenced perception on the need and importance of PA. Methods. Using data from 485 Portuguese subjects aged between 41 and 90 years old, differences between diabetics (n=85) and non-diabetics (n=400) were analyzed with Pearson's chi-square and independent t-test. Results. The study concludes that 32% of diabetics that are physically inactive. Their attitude toward PA is not much different from non-diabetics. Nevertheless, the importance given to the time available and the schedules of activities as well as exercising with friends were more relevant for diabetics. Diabetics considered that the exercise is not safe for their health condition and present lower expectation towards exercise. Regarding information seeking behavior about PA, diabetics use as leading information source doctors and less online information. Conclusion. Diabetics and non-diabetics give different importance to PA. Results establish a foundation for the development of effective tailored communication strategies to promote PA among the diabetics.